2018
DOI: 10.5152/tpd.2018.5330
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa, Metabolic Syndrome, and Demodex spp. Infestation

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease. This type of dermatosis with underlying chronic inflammation significantly affects the quality of life and may be accompanied by many comorbidities. In this case, Demodex spp. was associated with treatment-resistant and persistent course of skin diseases. A 46-year-old female patient applied to our clinic with complaints of lesions on the body and hip. Her dermatological examination revealed abscess formation and post-inflammatory pigmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The only diff erences in values for LDL between CD and control group (CG) were not statistically signifi cant. This observation contradicts the established data in the scientifi c literature, and its signifi cance and accuracy are to be further clarifi ed [45].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The only diff erences in values for LDL between CD and control group (CG) were not statistically signifi cant. This observation contradicts the established data in the scientifi c literature, and its signifi cance and accuracy are to be further clarifi ed [45].…”
Section: Discussionmentioning
confidence: 57%
“…The association of rosacea with impaired glucose tolerance is well documented in the scientifi c literature [6][7][8][9][10]21,[42][43][44]. On the other hand, data about the link between CD and prediabetes and diabetes is sparse [45]. For this reason, we investigated the association between CD with impaired glucose tolerance, defi ned as insulin resistance with a HOMA-IR index of over 2.7, prediabetes (with fasting glucose of 5.6 to 7 mmol/l or at the 120 th minute from the start of an oral glucose tolerance test of 7.8 to 11.0 mmol/l), and diabetes (with values for fasting glucose of over 7 mmol/l or at the 120 th from the start of an oral glucose tolerance test of over 11.0 mmol/l) [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…A case series found that four renal transplant recipients with the singular chief complaint of acne rosacea in fact had underlying demodicosis and their symptoms were responsive to appropriate treatment 13 . A case of persistent demodicosis has been reported in an immunocompetent patient whose other comorbidities included metabolic syndrome (diabetes mellitus, hypertension, and hyperlipidemia) and hidradenitis suppurativa 14 . Similarly, a number of case reports exist in the veterinary literature in which persistent, generalized demodicosis is described in immunocompetent animals with endocrine disorders 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…A 36-year-old woman with a past medical history significant for polycystic kidney disease and nephrolithiasis presented with a 9-month history of tender red bumps that would arise and burst over the span 14 Similarly, a number of case reports exist in the veterinary literature in which persistent, generalized demodicosis is described in immunocompetent animals with endocrine disorders. 15,16 Collectively, these data suggest that some combination of anatomic alterations, endocrine derangements and/or immune system deficiencies collectively exert an effect on the cutaneous microbiome that favors colonization/overgrowth of Demodex spp.…”
Section: Case Reportmentioning
confidence: 99%
“…Importantly, HS is associated with elevated levels of IgE ( 72 ), the antibody class central to anti-acarian immunity. HS is also linked to demodicosis ( 73 ), further supporting a role for dcd in anti-acarian immunity.…”
Section: Sweat Dermcidin and Anti-acarian Immunitymentioning
confidence: 99%